Early experience with the new endovascular aneurysm sealing system Nellix: First clinical results after 50 implantations. (August 2016) - Zerwes, Sebastian; Nurzai, Zmarai; Leissner, Giesbert; Kroencke, Thomas; Bruijnen, Hans-Kees; Jakob, Rudolf; Woelfle, Klaus
Objective: In the present study, 50 EVAS procedures were evaluated in regard to primary (survival and technical success) and secondary (device-related complications) events of interest. Methods: The single center study was conducted from July 2013 to August 2014 with prospective collection of the clinical data. The clinical results were controlled by CT angiography and contrast-enhanced ultrasound . Results: The technical success was 98% and the 30-day mortality 4%. One (2%) patient died from multisystem organ failure and another patient from an intracranial bleeding, respectively. One patient (2%) suffered from a device-related aneurysm rupture. During early follow-up, one (2%) patient developed an endoleak type II, while three (6%) patients suffered from a partial endograft limb thrombosis. Overall, a secondary intervention was necessary in six (12%) patients. Conclusions: With the Nellix EVAS system, a high primary technical success of 98% was achieved; one (2%) patient developed an endoleak type II which did not require secondary intervention. Those promising results are contrasted by a substantial rate of endograft limb thromboses (8%) and one (2%) intraoperative aneurysm rupture. Further studies are needed to assess the durability of the Nellix stentgraft and the occurrence of device-related complications.